1998
DOI: 10.1302/0301-620x.80b3.0800513
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical significance of bone bruises after supination injury of the ankle

Abstract: W e used MRI to study a prospective series of 95 patients with inversion injuries of the ankle and no fracture on plain radiographs. We found an incidence of bone bruises of 27%, but these made no difference to the time of return to work, limitation of walking or physical activity, or the clinical outcome scores at three months.We conclude that bone bruises have very little clinical significance after inversion injuries of the ankle.J Bone Joint Surg [Br] 1998;80-B:513-5. Received 26 September 1997; Accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…15,16 Mean age is 33years (18-64) in our study and right ankle being more commonly involved (71%) as it is dominant which is comparable to other studies. 3,[12][13][14][15] Anatomically sprains of the ankle can be divided into the lateral ligament, medial ligament and syndesmotic sprains of which the lateral ligament sprain induced by an inversion injury, which takes up 85% of ankle sprains, is the most common.…”
Section: Discussionsupporting
confidence: 87%
“…15,16 Mean age is 33years (18-64) in our study and right ankle being more commonly involved (71%) as it is dominant which is comparable to other studies. 3,[12][13][14][15] Anatomically sprains of the ankle can be divided into the lateral ligament, medial ligament and syndesmotic sprains of which the lateral ligament sprain induced by an inversion injury, which takes up 85% of ankle sprains, is the most common.…”
Section: Discussionsupporting
confidence: 87%
“…Several authors have reported the usefulness of MRI for diagnosing lateral ligament injuries, ¶ tibiofibular ligament injuries, 32,35,52 calcaneocuboid ligament injuries, 2 sinus tarsi syndrome, 24 tarsal tunnel syndrome, 16 peroneal tendon injury, 3,46 superficial peroneal nerve entrapment, 8 osteochondral lesions, 14 and osseous lesions including bone bruises. 1,23,40 However, MRI is not always more accurate than arthroscopy, especially in the diagnosis of tibiofibular ligament disruption or osteochondral lesions. 33,49 In the present study, advanced cases of grade III or IV lesions could be detected by preoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the inversion, the body's center of gravity moves over the ankle leading to ankle sprains [2]. There are three clinical grades of lateral ankle sprains [4][5][6].…”
Section: Biomechanicsmentioning
confidence: 99%
“…Even mild exacerbations lead to short-term dysfunction. It is characterized by residual ankle instability as a result of either mechanical ankle stability or functional ankle instability or a combination of both [6].…”
Section: Chronic Ankle Instability (Cai)mentioning
confidence: 99%